MATHEMATICAL PROBABILITY: LEARNER'S MISCONCEPTION IN A SELECTED SOUTH AFRICAN SCHOOL - Winston Hendricks; Babawande Emmanuel Olawale (IKIP Siliwangi and I-MES, 2023)
Mathematics plays an essential role in developing human thought, particularly in developing problem-solving and reasoning. While mathematics has become a problem-solving tool in various fields, including science, it has distinct qualities known as probability and, more specifically, probability theory. For most learners, the probability is difficult to learn and conceptualize. Hence, the present study investigates learners’ misconceptions in the teaching and learning of probability in a selected school in the Eastern Cape Province, South Africa. Underpinned by a Post-positivist paradigm, the study employed a quantitative research approach and a survey design in which data were gathered from mathematics learners from grades 10-12. Findings revealed that although the frequency of misconceptions varied across grade levels, it was difficult to describe how misconceptions about probability changed. As such, while learners progressed through the grades, some misconceptions faded with age, others remained stable, and others grew in power. The findings also revealed that the types of probability misconceptions did not differ significantly by gender, and male learners tend to have more misconceptions about probability than female learners.